Vanadium Pentoxide Nanorods Anchored to and Wrapped with Graphene Nanosheets for High‐Power Asymmetric Supercapacitors. Issue 9 (27th April 2015) - Li, Ge; Wang, Xiaolei; Hassan, Fathy M.; Li, Matthew; Batmaz, Rasim; Xiao, Xingcheng; Yu, Aiping
Abstract Asymmetric lithium‐ion supercapacitors have been obtaining great attention, owing to their significantly increased energy density. However, transition‐metal‐oxide‐based electrode materials with poor conductivity and sluggish electrode kinetics often sacrifice power performance and cycling stability. Herein, we report the in situ growth of V2O5 nanorods on highly conductive graphene sheets as anode materials with high specific capacitance and excellent rate capability, which is mainly attributed to the intimate contact between the nanorods and graphene sheets. The asymmetric supercapacitor based on graphene/V2O5 composites and activated carbon is fabricated and evaluated, where a high energy density of approximately 50 Wh kg−1 can be achieved at a power density of 136.4 W kg−1, as well as long cycling stability. This work provides an effective and efficient method for the fabrication of high‐performance asymmetric supercapacitors.